Psychophysics in functional strength and power training: Review and implementation framework - Ives, J. C.; Shelley, G. A. (The Journal of Strength and Conditioning Research, 2003)
Functional training is considered to be training that attempts to mimic the specific physiological demands of real-life activities. Most approaches to functional training, though, omit important factors that contribute to physiological and neuromotor adaptations. Cognitive factors related to sports influence physiological performance, and subsequently, physiological and neuromotor adaptations. We present a rationale and a theoretical framework by which to create effective functional training methods that incorporate cognitive factors. This framework draws upon recent developments and strong empirical evidence in the areas of dynamic systems theory, perceptual skills training, and motor learning/control. Emphasized within rigorous physical training are practice-related techniques and motor-learning strategies. In particular, mental effort, attention, and intention manipulated in a discovery-learning paradigm provide a framework for functional strength and power training. This framework is suggested to help maximize sport-specific physiological adaptations, and subsequently, sports performance.